Linear accelerator for security, industrial and medical applications with rapid beam parameter variation. (June 2021) - Kutsaev, S.V.; Agustsson, R.; Arodzero, A.; Berry, R.; Boucher, S.; Diego, A.; Gavryushkin, D.; Hartzell, J.J.; Lanza, R.C.; Smirnov, A.Yu.; Verma, A.; Ziskin, V.
Abstract: RadiaBeam has developed a novel, flexible linac for electrons and X-rays (FLEX) capable of energy variation from 2 to 9 MeV within a single RF pulse. This accelerator employs a robust traveling wave accelerating structure with a large energy and power acceptance that allows the unique features of deep energy and current variation required for novel adaptive cargo inspection techniques and Computed Tomography. Robust RF and water-cooling systems allow average beam powers up to 15 kW, upgradable to 57 kW, at 6 MeV, potentially making this accelerator useful for electron beam irradiation applications. The high peak currents of the electron beam produced by FLEX enable novel FLASH radiotherapy methods with fast dose delivery. In this paper, we present the linac design and its components, as well the results of the experimental demonstration of beam acceleration with energy variation. Highlights: Novel security, radiotherapy and industrial applications require new accelerators. Adaptive cargo inspection needs beam parameters variation within a single pulse. FLASH radiotherapy requires delivery of high X-ray doses within a few seconds. RadiaBeam developed accelerator with rapid beam energy and current variation.